2021
DOI: 10.1094/phyto-09-20-0431-r
|View full text |Cite
|
Sign up to set email alerts
|

The FgCYP51B Y123H Mutation Confers Reduced Sensitivity to Prochloraz and Is Important for Conidiation and Ascospore Development in Fusarium graminearum

Abstract: Fusarium graminearum is one of the most important causal agent of Fusarium Head Blight disease and now were controlled mainly by chemicals such as DMI fungicides. FgCYP51B is one of the DMI targets in F. graminearum and Tyrosine123 is an important amino acid in Fusarium graminearum CYP51B, located in one of the predicted substrate binding pockets based on the binding mode between demethylation inhibitors (DMIs) and CYP51B. Previous study suggests that resistance to DMI fungicides is primarily attributed to poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…In recent years, food safety has become an important topic, and synthetic fungicides have been shown to cause serious health problems in humans [38][39][40]. Moreover, F. graminearum has developed resistance to synthetic fungicides, such as azoles and carbendazim, because of their long-term usage [41][42][43][44][45]. Therefore, it is of great significance to develop active ingredients of biological fungicides to combat this critical pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, food safety has become an important topic, and synthetic fungicides have been shown to cause serious health problems in humans [38][39][40]. Moreover, F. graminearum has developed resistance to synthetic fungicides, such as azoles and carbendazim, because of their long-term usage [41][42][43][44][45]. Therefore, it is of great significance to develop active ingredients of biological fungicides to combat this critical pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the amino acid mutations Y137H and Y123H on the FgCYP51B gene can give rise to resistance (Qian et al., 2018; Zhao et al., 2021). In other diseases, mutation of the CYP51 gene also causes fungicide resistance.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the production of conidia, these strains were cultured in carboxymethyl cellulose (CMC) liquid medium. All the strains were stored in 15% glycerol at −80 °C [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…All F. graminearum strains were grown on potato dextrose agar (PDA), spezieller nährstoffarmer agar (SNA), or potato dextrose broth (PDB) liquid medium at 25 • C. To determine the production of conidia, these strains were cultured in carboxymethyl cellulose (CMC) liquid medium. All the strains were stored in 15% glycerol at −80 • C [51].…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%